Interest Rate Liberalization and Firm Leverage in China: Effects and Channels - Caiyun Chen; Xuefei Peng; Liufang Yu (Discrete Dynamics in Nature and Society)
We examine whether and how interest rate liberalization affects firm leverage in China. We find that interest rate liberalization exerts a negative effect on the leverage of firms. Specifically, firms experience a reduction in total leverage during the liberalization period, and firms’ short-term leverage declines more relative to long-term leverage. Mechanism analysis shows that firms with high information asymmetry enjoy more decline in leverage relative to firms with low information asymmetry, and further, liberalization policy enables the reduction in credit transaction costs, which indicates that the behavior of banks actively collecting corporate information is an important channel that interest rate liberalization impacts firm leverage. Finally, in additional tests, we find that the impact is more salient when firms are non-state-owned, and loss making. Compare to operating liabilities, firms experience more reduction in financial liability.